Development of best practice recommendations to enhance access to and use of formal community care services for people with dementia in Europe - Røsvik, Janne (2022)
Funding: The Research Council of Norway; Portugal, Foundation for Science and Technology (FCT - JPND-HC/0001/2012); the United Kingdom, Economic and Social Research Council. The funding organisations did not influence the design of the study or the content of the manuscript